Bat and moth in flight pictures, 1 - Unknown (Tufts Archival Research Center, 2019)
This is the digital version of 2 catches and a miss; you can see where the moth and the bat are, and that their paths intersect in the first two shots, but the moth escapes in the third shot. These were shot at night in nature, probably in Concord, MA.